Double-layer packaging adhesive film and preparation method and application thereof
By adopting a double-layer encapsulated film structure in photovoltaic modules, including thermoplastic layer and crosslinking layer, the problem of difficulty in disassembly and recycling of photovoltaic modules is solved, convenient disassembly and efficient recycling of components is achieved, and anti-PID performance is improved.
Patent Information
- Application Number
- CN202411995725.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The packaging film of existing photovoltaic modules is difficult to disassemble and recycle after the components are scrapped, resulting in waste of resources and environmental pollution.
A double-layer encapsulated film structure is adopted, including a thermoplastic layer and a crosslinking layer. By setting the thermoplastic layer and the crosslinking layer, the hot melt disassembly of the photovoltaic module at a high temperature of 180-200℃, and the components are guaranteed to resist PID and aging resistance.
It realizes convenient disassembly and recycling of photovoltaic modules, reduces production costs, improves production efficiency, and improves the anti-PID performance of the modules by reducing ion penetration.
Smart Images

Figure CN119752346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic adhesive films, and in particular to a double-layer encapsulation adhesive film and a preparation method and application thereof. Background Art
[0002] Solar energy is a renewable energy source. It has attracted widespread attention in recent years because of its advantages such as cleanliness, environmental protection and renewability. Photovoltaic modules are devices that convert solar energy into electrical energy. They are mainly composed of tempered glass, encapsulation film, crystalline silicon solar cells, encapsulation film, backplane, etc. With the increasing annual installed capacity of solar power generation, the scrapping, recycling and reuse of modules have become a difficult problem faced by the photovoltaic industry. However, the encapsulation film is formed into a three-dimensional stable structure through high-temperature lamination. When the cell fails, it cannot be hot-melted and peeled off, making it difficult to recycle the film and the module, making it difficult to disassemble and recycle the photovoltaic module.
[0003] At present, there are mainly the following methods for recycling photovoltaic modules: for framed modules, the physical separation method is first used to manually disassemble the aluminum frame, glass and junction box to obtain frameless modules. This method is time-consuming and labor-intensive, and the dusty environment processing is harmful to human health; for frameless modules, one method is to use an incinerator to incinerate the crushed photovoltaic modules, so as to separate and recycle the battery cells, glass and welding strips. The products obtained by this method are mostly crushed glass and broken battery cells, which are difficult to screen and separate, wasting a lot of manpower and material costs, and there is a large material loss in the separation, and the valuable materials cannot be fully recycled; the other method is to place the photovoltaic module in a container containing an inorganic acid or organic acid solution, and dissolve the encapsulation film in the photovoltaic module to separate the battery cells from the glass. The recycling cycle is long, and the waste liquid treatment is difficult in the later stage.
[0004] CN115141555A discloses a recyclable and peelable photovoltaic adhesive film. By setting a three-layer sandwich structure, the cross-linked layer has the excellent anti-PID, adhesion and weather resistance of the traditional cross-linked adhesive film in the packaging of the crystalline silicon module, and the thermoplastic layer can be used to achieve hot melting at 170-230°C, which is convenient for peeling off from materials such as glass, battery cells and backplanes, so that the adhesive film and photovoltaic modules can be recycled. However, designing a double-layer adhesive film structure that is simpler than the three-layer adhesive film is more helpful in reducing production costs and improving production efficiency. It can also improve the anti-PID (potential induced decay) performance of the module by reducing the number of ions passing through the adhesive film layer to reach the surface of the battery cell. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a double-layer packaging film and a preparation method and application thereof. By setting a thermoplastic layer and a cross-linking layer, the obtained double-layer packaging film has a power attenuation of <3.5% after PID192h, a front attenuation of 0.87%-3.05%, a back attenuation of 0.80%-2.98%, a light transmittance of 89.32%-92.2%, and a peeling force between the thermoplastic layer and the glass of 46-63N / cm. The photovoltaic module containing the double-layer packaging film prepared by the present invention can be hot-melt disassembled at 180-200°C, thereby realizing convenient disassembly and recycling of the photovoltaic module.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a double-layer packaging adhesive film, wherein the double-layer packaging adhesive film comprises a thermoplastic layer and a cross-linking layer.
[0008] The raw materials for preparing the thermoplastic layer include modified resin, inorganic filler and weather resistance additive.
[0009] The raw materials for preparing the cross-linking layer include a first main resin, a cross-linking agent and an auxiliary cross-linking agent.
[0010] The present invention provides a thermoplastic layer and a cross-linking layer, so that the component can be hot-melt disassembled at a high temperature of 180-200°C while ensuring good adhesion to the front plate or back plate of the photovoltaic component, excellent optical properties of the entire component, and good anti-PID performance and aging resistance.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, the raw materials for preparing the thermoplastic layer include the following components in parts by weight:
[0013] 86-109 parts of modified resin;
[0014] Inorganic filler 0.1-0.5 parts;
[0015] Weather resistance additive 0.1-2 parts.
[0016] Among them, the modified resin can be 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 96 parts, 98 parts, 100 parts, 102 parts, 104 parts, 106 parts, 108 parts or 109 parts, etc.
[0017] The inorganic filler may be 0.1 part, 0.2 part, 0.3 part, 0.4 part or 0.5 part, etc.
[0018] The amount of the weather resistance additive may be 0.1 part, 0.5 part, 1 part, 1.5 parts or 2 parts.
[0019] Preferably, the softening point of the modified resin is greater than 80°C, for example, 82°C, 85°C, 90°C or 95°C.
[0020] Preferably, the melt index of the modified resin is 2-10 g / 10 min (190°C / 5 kg), for example, it may be 2 g / 10 min (190°C / 5 kg), 4 g / 10 min (190°C / 5 kg), 6 g / 10 min (190°C / 5 kg), 8 g / 10 min (190°C / 5 kg) or 10 g / 10 min (190°C / 5 kg), etc.
[0021] Preferably, the modified resin is a graft copolymer obtained by grafting the second main resin with a compound monomer.
[0022] Preferably, the second main resin includes any one of EVA, POE, PP, polyamide resin, SBS or SEBS, or a combination of at least two thereof.
[0023] Preferably, the compound monomer includes any one of maleic anhydride, acrylic acid, butyl acrylate or silane monomer, or a combination of at least two thereof.
[0024] Preferably, the preparation method of the modified resin comprises the following steps:
[0025] The second main resin, the initiator and the compound monomer are mixed and granulated in a twin-screw extruder to react to obtain the modified resin.
[0026] Preferably, the temperature of the mixing and granulation is 200-220°C, for example, 200°C, 205°C, 210°C, 215°C or 220°C.
[0027] Preferably, the grafting reaction time is 10-20 s, for example, it can be 10 s, 12 s, 14 s, 16 s, 18 s or 20 s.
[0028] Preferably, the initiator comprises dicumyl peroxide.
[0029] Preferably, the grafting rate of the modified resin is 1.0-2.0%, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, etc.
[0030] Preferably, the inorganic filler includes any one of calcium carbonate, talc, barium sulfate, wollastonite, kaolin, clay or ceramic microbeads, or a combination of at least two thereof.
[0031] Preferably, the weather resistance additive includes any one of an antioxidant, an ultraviolet light absorber or a light stabilizer, or a combination of at least two of them.
[0032] Preferably, the content of the antioxidant in the weather resistance additive is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0033] Preferably, the content of the ultraviolet light absorber in the weather resistance additive is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0034] Preferably, the content of the light stabilizer in the weather resistance additive is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0035] Preferably, the antioxidant includes antioxidant 1010 and / or antioxidant 168.
[0036] Preferably, the ultraviolet light absorber includes any one of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol, 2,4-dihydroxybenzophenone or phenyl salicylate, or a combination of at least two thereof.
[0037] Preferably, the light stabilizer includes any one or a combination of at least two of bis-2,2,6,6-tetramethylpiperidinol sebacate, bis-2,2,6,6-tetramethylpiperidinol sebacate, a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-sebacate or methyl-1,2,2,6,6-pentamethyl-4-piperidinyl sebacate.
[0038] Preferably, the raw materials for preparing the cross-linking layer include the following components in parts by weight:
[0039] 85-99 parts of the first main resin;
[0040] Cross-linking agent 0.2-1 part;
[0041] Auxiliary cross-linking agent 0.1-0.8 parts.
[0042] Among them, the first main resin can be 85 parts, 87 parts, 89 parts, 91 parts, 93 parts, 95 parts, 97 parts or 99 parts, etc.
[0043] The cross-linking agent may be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts or 1 part, etc.
[0044] The amount of the auxiliary cross-linking agent may be 0.1 part, 0.2 part, 0.4 part, 0.6 part or 0.8 part.
[0045] Preferably, the first main resin in the cross-linked layer includes any one of EVA, POE or EPE, or a combination of at least two of them.
[0046] Preferably, the crosslinking agent in the crosslinking layer comprises tert-amyl peroxy(2-ethylhexyl)carbonate and / or tert-butyl peroxy(2-ethylhexyl)carbonate.
[0047] Preferably, the auxiliary cross-linking agent in the cross-linking layer includes any one of triallyl isocyanurate, trimethylolpropane triacrylate or ethoxylated glycerol triacrylate, or a combination of at least two thereof.
[0048] Preferably, the raw materials for preparing the cross-linking layer further include any one of a silane coupling agent, an antioxidant or an ultraviolet light absorber, or a combination of at least two of them.
[0049] Preferably, the content of the silane coupling agent in the raw material for preparing the cross-linking layer is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0050] Preferably, the content of the antioxidant in the raw material for preparing the cross-linked layer is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0051] Preferably, the content of the ultraviolet light absorber in the raw material for preparing the cross-linking layer is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0052] Preferably, the silane coupling agent in the cross-linking layer includes any one of vinyl trimethoxy silane, vinyl triethoxy silane or vinyl tri-tert-butyl peroxy silane, or a combination of at least two thereof.
[0053] Preferably, the antioxidant in the cross-linked layer includes any one of antioxidant 1010, antioxidant 168 or antioxidant 1076, or a combination of at least two of them.
[0054] Preferably, the ultraviolet light absorber includes any one of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol, 2,4-dihydroxybenzophenone or phenyl salicylate, or a combination of at least two thereof.
[0055] Preferably, the thickness of the thermoplastic layer is 10-500 μm, for example, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm, etc., more preferably 100-200 μm;
[0056] Preferably, the thickness of the cross-linked layer is 100-500 μm, for example, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm, etc., more preferably 300-400 μm.
[0057] In a second aspect, the present invention provides a method for preparing the double-layer encapsulation film as described in the first aspect, the preparation method comprising the following steps:
[0058] (1) mixing a second main resin, an initiator and a compound monomer uniformly, adding the mixture to a twin-screw extruder, extruding and granulating the mixture to obtain the modified resin, drying the modified resin, and then mixing the dried modified resin with an inorganic filler and a weathering agent, and after mixing the mixture uniformly, extruding and casting the mixture at 160-170° C. to obtain the thermoplastic layer;
[0059] The first main resin, the crosslinking agent, the auxiliary crosslinking agent, the optional silane coupling agent and the optional antioxidant are uniformly mixed and then extruded and cast at 100-110° C. to obtain the crosslinking layer.
[0060] (2) The thermoplastic layer and the cross-linked layer obtained in step (1) are laminated together using a roller laminator to obtain the double-layer packaging film.
[0061] Preferably, in the method for preparing the thermoplastic layer in step (1), the temperature of the twin-screw extruder is set to 200-220°C (for example, 200°C, 205°C, 210°C, 215°C or 220°C), and the time is 10-20s (for example, 10s, 12s, 14s, 16s, 18s or 20s).
[0062] Preferably, the temperature of the roller laminating machine in step (2) is set to 70-90°C, for example, 70°C, 75°C, 80°C, 85°C or 90°C.
[0063] In a third aspect, the present invention provides a use of the double-layer packaging film as described in the first aspect in a photovoltaic cell assembly.
[0064] Preferably, the thermoplastic layer in the double-layer encapsulation film is bonded to the front plate or back plate in the photovoltaic module. The cross-linked layer in the double-layer encapsulation film is bonded to the cell in the photovoltaic module.
[0065] Compared with the prior art, the present invention has at least the following beneficial effects:
[0066] (1) The present invention provides a double-layer encapsulation film, including a thermoplastic layer and a cross-linking layer. The setting of the thermoplastic layer can enable the photovoltaic module to be hot-melt disassembled at a high temperature of 180-200°C while ensuring good adhesion with the photovoltaic front panel or back panel and excellent optical performance of the module as a whole, thereby realizing convenient disassembly and recycling of the photovoltaic module; the setting of the cross-linking layer can ensure that the module has good anti-PID performance and aging resistance.
[0067] (2) Specifically, the double-layer encapsulation film prepared by the present invention has a power attenuation of <3.5% after PID192h, a front attenuation of 0.87%-3.05%, a back attenuation of 0.80%-2.98%, a light transmittance of 89.32%-92.2%, and a peeling force between the thermoplastic layer and the glass of 46-63N / cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is a schematic diagram of the structure of the double-layer packaging film in the present invention:
[0069] 1- Thermoplastic layer; 2- Cross-linked layer. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0071] In the following specific implementation of the present invention, the specific information of the materials used is as follows:
[0072] 1. SEBS resin, W1G, purchased from Coase Chemical;
[0073] 2. EVA resin, TL-V2825, purchased from Xinjiang Tianli;
[0074] 3. POE resin, LF575, purchased from LG Chemical.
[0075] Example 1
[0076] A double-layer packaging adhesive film comprises a thermoplastic layer and a cross-linking layer.
[0077] The method for preparing the thermoplastic layer comprises the following steps:
[0078] 98.95 parts of SEBS resin, 0.5 parts of diisopropylbenzene peroxide and 5 parts of maleic anhydride are added into a twin-screw extruder, and grafted and modified for 15 seconds at 200°C to obtain a modified resin. The modified resin is dried, and then 104 parts of the dried modified resin, 0.5 parts of calcium carbonate, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.15 parts of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol are mixed evenly, and extruded and cast at 160°C to obtain the thermoplastic layer.
[0079] The grafting rate of the modified resin was 1.6%.
[0080] The thickness of the thermoplastic layer is 100 μm.
[0081] The preparation method of the cross-linked layer comprises the following steps:
[0082] 98.95 parts of EVA resin, 0.6 parts of tert-butyl peroxycarbonate-2-ethylhexyl, 0.5 parts of triallyl isocyanurate (TAIC, purchased from Hunan Minhe), 0.4 parts of vinyl trimethoxysilane, 0.2 parts of antioxidant 1010 and 0.15 parts of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol were mixed evenly and added into a casting extruder, and the temperature was set to 100° C. to obtain the cross-linked layer.
[0083] The thickness of the cross-linked layer is 400 μm.
[0084] The preparation method of the double-layer packaging film comprises the following steps:
[0085] The extrusion cast thermoplastic layer and the cross-linked layer are stacked and placed, and the thermoplastic layer and the cross-linked layer are covered with release paper, and after being laminated by a roller laminator, the release paper is removed to obtain the double-layer packaging film.
[0086] The temperature of the roll laminator was set at 80°C.
[0087] Example 2
[0088] A double-layer packaging adhesive film comprises a thermoplastic layer and a cross-linking layer.
[0089] The method for preparing the thermoplastic layer comprises the following steps:
[0090] 98.95 parts of SEBS resin, 0.5 parts of diisopropylbenzene peroxide and 5 parts of maleic anhydride are added into a twin-screw extruder, and grafted and modified for 15 seconds at 200°C to obtain a modified resin. The modified resin is dried, and then 104 parts of the dried modified resin, 0.5 parts of calcium carbonate, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.15 parts of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol are mixed evenly, and extruded and cast at 160°C to obtain the thermoplastic layer.
[0091] The grafting rate of the modified resin was 1.6%.
[0092] The thickness of the thermoplastic layer is 100 μm.
[0093] The preparation method of the cross-linked layer comprises the following steps:
[0094] 98.95 parts of POE resin, 0.6 parts of tert-butyl peroxycarbonate-2-ethylhexyl, 0.5 parts of triallyl isocyanurate (TAIC, purchased from Hunan Minhe), 0.4 parts of vinyl trimethoxysilane, 0.2 parts of antioxidant 1010 and 0.15 parts of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol were mixed evenly and added to a casting extruder, and the temperature was set to 100° C. to obtain the cross-linked layer.
[0095] The thickness of the cross-linked layer is 400 μm.
[0096] The preparation method of the double-layer packaging film comprises the following steps:
[0097] The extrusion cast thermoplastic layer and the cross-linked layer are stacked and placed, and the thermoplastic layer and the cross-linked layer are covered with release paper, and after being laminated by a roller laminator, the release paper is removed to obtain the double-layer packaging film.
[0098] The temperature of the roll laminator was set at 80°C.
[0099] Example 3
[0100] A double-layer packaging film, which differs from Example 1 in that the modified resin comprises 98.95 parts of SEBS resin, 0.2 parts of dicumyl peroxide, and 2 parts of maleic anhydride, and the grafting rate of the modified resin is 1.0%.
[0101] Example 4
[0102] A double-layer packaging film, which differs from Example 1 in that the modified resin comprises 98.95 parts of SEBS resin, 0.3 parts of dicumyl peroxide, and 3 parts of maleic anhydride, and the grafting rate of the modified resin is 1.2%.
[0103] Example 5
[0104] A double-layer packaging film, which differs from Example 1 in that the modified resin comprises 98.95 parts of SEBS resin, 0.4 parts of dicumyl peroxide, and 4 parts of maleic anhydride, and the grafting rate of the modified resin is 1.4%.
[0105] Example 6
[0106] A double-layer packaging film, which differs from Example 1 in that the modified resin comprises 98.95 parts of SEBS resin, 0.6 parts of dicumyl peroxide, and 8 parts of maleic anhydride, and the grafting rate of the modified resin is 1.8%.
[0107] Example 7
[0108] A double-layer packaging film, which differs from Example 1 in that the modified resin comprises 98.95 parts of SEBS resin, 0.8 parts of dicumyl peroxide, and 10 parts of maleic anhydride, and the grafting rate of the modified resin is 2.3%.
[0109] Example 8
[0110] A double-layer packaging film, which differs from Example 1 in that the thickness of the thermoplastic layer is 120 μm, and the thickness of the cross-linking layer is 380 μm.
[0111] Example 9
[0112] A double-layer packaging film, which differs from Example 1 in that the thickness of the thermoplastic layer is 140 μm, and the thickness of the cross-linking layer is 360 μm.
[0113] Example 10
[0114] A double-layer packaging film, which differs from Example 1 in that the thickness of the thermoplastic layer is 160 μm, and the thickness of the cross-linking layer is 340 μm.
[0115] Embodiment 11
[0116] A double-layer packaging film, which differs from Example 1 in that the thickness of the thermoplastic layer is 180 μm, and the thickness of the cross-linking layer is 320 μm.
[0117] Example 12
[0118] A double-layer packaging film, which differs from Example 1 in that the thickness of the thermoplastic layer is 200 μm, and the thickness of the cross-linking layer is 300 μm.
[0119] Example 13
[0120] A double-layer packaging film, which differs from Example 1 in that the thickness of the thermoplastic layer is 50 μm, and the thickness of the cross-linking layer is 490 μm.
[0121] Comparative Example 1
[0122] A double-layer packaging film, which differs from Example 1 in that no thermoplastic layer is provided, only a cross-linked layer is included, and the thickness is 500 μm. Other structures, materials and preparation methods are the same as those of Example 1.
[0123] Comparative Example 2
[0124] A double-layer packaging film, which differs from Example 1 in that no cross-linking layer is provided, only a thermoplastic layer is included, and the thickness is 500 μm. Other structures, materials and preparation methods are the same as those of Example 1.
[0125] Comparative Example 3
[0126] A double-layer packaging film is provided. The difference between the double-layer packaging film and the embodiment 1 is that the modified SEBS resin is replaced by the common SEBS resin WG1 in the thermoplastic layer. The other structures, materials and preparation methods are the same as those in the embodiment 1.
[0127] The performance of the high double-layer encapsulation films provided in the above embodiments and comparative examples was characterized, and the specific testing method was as follows:
[0128] Peel force (N / cm): The test is carried out in accordance with the GB / T 29848-2018 standard;
[0129] Film yellowing coefficient Δb (UV60KWh): tested in accordance with GB / T39822-2021 standard;
[0130] Light transmittance (%): The test is carried out in accordance with the GB / T 29848-2018 standard;
[0131] EL (electroluminescence) after lamination: tested in accordance with IEC 61215 and IEC 61730 standards;
[0132] TC400 post-EL: Tested in accordance with IEC 61215 and IEC 61730 standards;
[0133] Anti-PID performance (%): Tested in accordance with the IEC61215-2020 standard;
[0134] Hot spot test method: first connect the component to a 30-40 mA current, then place it in a 200°C oven for 1 hour, and then check the appearance of the component;
[0135] DH1000h performance (%): The test is carried out in accordance with the "IEC61215" standard;
[0136] Grafting rate: Determined by acid-base titration method, the specific method is:
[0137] Weigh about 0.2g of modified resin sample with an electronic balance, place it in a 250mL three-necked bottle, add 50mL of xylene and 25mL of ethanol solution, and drop 1-2mL of water and DMF. Heat at 120℃ for 2h, then titrate the solution while hot with 0.1mol / L KOH / ethanol solution, using thymol blue as the indicator.
[0138] The grafting rate of SEBS-g-MAH can be expressed by the following equation:
[0139] Grafting rate = [(V1C1-V2C1) × 56.11 × 1000 / W] × 100%;
[0140] Where:
[0141] W—mass of SEBS-g-MAH sample (g);
[0142] V1—volume of KOH / ethanol solution consumed by the mixed solution to be tested (mL);
[0143] C1—concentration of KOH / ethanol solution (mol / L);
[0144] V2—volume of KOH / ethanol solution consumed by the blank xylene / ethanol mixed solution (mL); 56.11—constant, molar mass of KOH (g / mol).
[0145] Test Results
[0146] The double-layer packaging films provided in Examples 1-13 and Comparative Examples 1-3 were tested according to the above test method. The test results are shown in Table 1-2:
[0147] Table 1
[0148]
[0149] Table 2
[0150]
[0151] The test results show that:
[0152] (1) It can be seen from Examples 1 to 2 that the present invention can achieve hot melt disassembly of the components at a high temperature of 180-200°C by providing a thermoplastic layer and a cross-linking layer, and ensure that the components have good PID performance and aging resistance.
[0153] When the cross-linking layer is a POE layer, the yellowing index of the film increases, the EL display has a shadow after TC400, and the transmittance will decrease, but the component PID power attenuation is reduced, the component disassembly temperature is lowered, and the impact on the component hot spot is small, which can basically meet the requirements.
[0154] (2) It can be seen from Examples 3 to 6 that, as the grafting rate of the modified resin of the present invention increases, the fluidity of the film decreases and the peeling force with glass increases; the grafting rate also affects the yellowing coefficient of the film. As the grafting rate increases, the light transmittance decreases slightly, the PID power attenuation decreases, and the temperature at which the component can be disassembled increases, all of which meet the requirements. However, it can be seen from Claim 7 that the grafting rate cannot be increased indefinitely, which will affect the stability of the film and lead to a decrease in various properties such as the film viscosity.
[0155] (3) It can be seen from Examples 8 to 12 that as the thickness of the thermoplastic layer increases, the damp heat aging power attenuation of the component increases, so the thickness of the thermoplastic layer cannot be increased indefinitely. However, it can be seen from Claim 13 that the thickness of the thermoplastic layer cannot be too small, otherwise the component cannot be disassembled at 180-200°C.
[0156] (4) It can be seen from Example 1 and Comparative Examples 1-2 that if the adhesive film does not include a thermoplastic layer, the component cannot be disassembled under the condition of 180-200°C; if the adhesive film does not include a cross-linking layer, the anti-PID power attenuation, wet heat aging power and other performances of the component are all unqualified, and hot melt disassembly cannot be performed.
[0157] (5) It can be seen from Example 1 and Comparative Example 3 that the components made of the encapsulation film provided in Comparative Example 3 are not up to standard in terms of anti-PID attenuation performance, hot spot test appearance, DH1000h and other performances.
[0158] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A double-layer packaging film, characterized in that: The double-layer packaging film comprises a thermoplastic layer and a cross-linking layer; The raw materials for preparing the thermoplastic layer include modified resin, inorganic filler and weather-resistant additive; The raw materials for preparing the cross-linking layer include a first main resin, a cross-linking agent and an auxiliary cross-linking agent.
2. The double-layer packaging film according to claim 1, characterized in that: The raw materials for preparing the thermoplastic layer include the following components in parts by weight: 86-109 parts of modified resin; Inorganic filler 0.1-0.5 parts; Weathering agent 0.1-2 parts; Preferably, the softening point of the modified resin is greater than 80°C; Preferably, the melt index of the modified resin is 2-10 g / 10 min (190° C. / 5 kg).
3. The double-layer packaging film according to claim 1 or 2, characterized in that: The modified resin is a graft copolymer obtained by grafting the second main resin with the compound monomer; Preferably, the second main resin includes any one of EVA, POE, PP, polyamide resin, SBS or SEBS, or a combination of at least two thereof; Preferably, the compound monomer includes any one or a combination of at least two of maleic anhydride, acrylic acid, butyl acrylate or silane monomer; Preferably, the preparation method of the modified resin comprises the following steps: The second main resin, the initiator and the compound monomer are mixed in a twin-screw extruder to react to obtain the modified resin; Preferably, the mixing temperature is 200-220°C; Preferably, the mixing time is 10-20s; Preferably, the initiator comprises dicumyl peroxide; Preferably, the grafting rate of the modified resin is 1.0-2.0%.
4. The double-layer packaging film according to any one of claims 1 to 3, characterized in that: The inorganic filler includes any one of calcium carbonate, talc, barium sulfate, wollastonite, kaolin, clay or ceramic microbeads, or a combination of at least two thereof.
5. The double-layer packaging film according to any one of claims 1 to 4, characterized in that: The weather resistance additive includes any one of an antioxidant, an ultraviolet light absorber or a light stabilizer, or a combination of at least two thereof; Preferably, the content of the antioxidant in the weather resistance additive is 0.1-1 part; Preferably, the content of the ultraviolet light absorber in the weather resistance additive is 0.1-1 part; Preferably, the content of the light stabilizer in the weather resistance additive is 0.1-1 part; Preferably, the antioxidant includes antioxidant 1010 and / or antioxidant 168; Preferably, the ultraviolet light absorber includes any one or a combination of at least two of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol, 2,4-dihydroxybenzophenone or phenyl salicylate; Preferably, the light stabilizer includes any one or a combination of at least two of bis-2,2,6,6-tetramethylpiperidinol sebacate, bis-2,2,6,6-tetramethylpiperidinol sebacate, a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-sebacate or methyl-1,2,2,6,6-pentamethyl-4-piperidinyl sebacate.
6. The double-layer packaging film according to any one of claims 1 to 5, characterized in that: The raw materials for preparing the cross-linked layer include the following components in parts by weight: 85-99 parts of the first main resin; Cross-linking agent 0.2-1 part; 0.1-0.8 parts of auxiliary cross-linking agent; Preferably, the first main resin in the cross-linked layer includes any one of EVA, POE or EPE or a combination of at least two thereof; Preferably, the crosslinking agent in the crosslinking layer comprises tert-amyl peroxy (2-ethylhexyl) carbonate and / or tert-butyl peroxy carbonate-2-ethylhexyl; Preferably, the auxiliary cross-linking agent in the cross-linking layer includes any one of triallyl isocyanurate, trimethylolpropane triacrylate or ethoxylated glycerol triacrylate, or a combination of at least two thereof.
7. The double-layer packaging film according to any one of claims 1 to 6, characterized in that: The raw materials for preparing the cross-linked layer also include any one or a combination of at least two of a silane coupling agent, an antioxidant or an ultraviolet light absorber; Preferably, the content of the silane coupling agent in the raw material for preparing the cross-linking layer is 0.1-1 part; Preferably, the content of antioxidant in the raw materials for preparing the cross-linked layer is 0.1-1 part; Preferably, the content of the ultraviolet light absorber in the raw materials for preparing the cross-linking layer is 0.1-1 part; Preferably, the silane coupling agent in the cross-linking layer includes any one of vinyl trimethoxy silane, vinyl triethoxy silane or vinyl tri-tert-butyl peroxy silane or a combination of at least two thereof; Preferably, the antioxidant in the cross-linked layer includes any one of antioxidant 1010, antioxidant 168 or antioxidant 1076, or a combination of at least two thereof; Preferably, the ultraviolet light absorber includes any one of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol, 2,4-dihydroxybenzophenone or phenyl salicylate, or a combination of at least two thereof.
8. The double-layer packaging film according to any one of claims 1 to 7, characterized in that: The thickness of the thermoplastic layer is 10-500 μm, more preferably 100-200 μm; Preferably, the thickness of the cross-linked layer is 100-500 μm, more preferably 300-400 μm.
9. A method for preparing a double-layer packaging film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) mixing a second main resin, an initiator and a compound monomer uniformly, adding the mixture to a twin-screw extruder, extruding and granulating the mixture to obtain the modified resin, drying the modified resin, and then mixing the dried modified resin with an inorganic filler and a weathering agent, and after mixing the mixture uniformly, extruding and casting the mixture at 160-170° C. to obtain the thermoplastic layer; The first main resin, the crosslinking agent, the auxiliary crosslinking agent, the optional silane coupling agent and the optional antioxidant are uniformly mixed and then extruded and cast at 100-110° C. to obtain the crosslinked layer; (2) laminating the thermoplastic layer and the cross-linked layer obtained in step (1) by means of a roller laminator to obtain the double-layer packaging film; Preferably, in the method for preparing the thermoplastic layer in step (1), the operating temperature of the twin-screw extruder is 200-220°C; Preferably, in the method for preparing the thermoplastic layer in step (1), the operation time of the twin-screw extruder is 10-20 seconds; Preferably, the temperature of the roller laminating machine in step (2) is set to 70-90°C.
10. Application of the double-layer encapsulation film according to any one of claims 1 to 6 in a photovoltaic cell assembly; Preferably, the thermoplastic layer in the double-layer encapsulation film is bonded to the front plate or the back plate in the photovoltaic module, and the cross-linking layer in the double-layer encapsulation film is bonded to the battery cell in the photovoltaic module.
Citation Information
Patent Citations
Anti-PID POE adhesive film special for photovoltaic double-glass assembly packaging and preparation method thereof
CN111518487A
LED packaging adhesive film, application of LED packaging adhesive film and LED packaging structure
CN114149755A
Recyclable and peelable photovoltaic adhesive film
CN115141555A
Glue solution of high-antistatic-performance cover tape for semiconductor chip packaging and preparation method and coating method thereof
CN117946609A